Realizing forming-free characteristic by doping Ag into HfO2-based RRAM. (26th March 2021) - Wu, Chung-Wei; Lin, Chun-Chu; Chen, Po-Hsun; Chang, Ting-Chang; Zhou, Kuan-Ju; Chen, Wen-Chung; Tan, Yung-Fang; Yeh, Yu-Hsuan; Chou, Sheng-Yao; Huang, Hui-Chun; Tsai, Tsung-Ming; Sze, Simon M.
Abstract: In this work, Ag-doped HfO2 -based resistive random access memory (RRAM) with high on-off ratio, low-power consumption and forming-free properties was investigated. We propose the fabrication flow of the RRAM with via-hole structure. After doping Ag into HfO2 as the switching layer, the devices could execute resistive switching without a high-voltage forming process. The conduction mechanism was subsequently validated by a current fitting analysis. Electric field simulation was also utilized to observe the electric field distribution and finally a physical model was proposed to provide an explanation for the formation and dissolution of the filament.